PENGUJIAN SENYAWA BAHAN ALAM PADA SISTEM PENAPISAN DENGAN TARGET DIMERISASI DOMAIN SITOPLASMIK PhoR Mycobacterium tuberculosis - Alifia, Almira
One of the main problems encountered in the treatment of tuberculosis is antibiotic resistance. About 4-19% of tuberculosis patients have Multidrug Resistant Tuberculosis (MDR-TB) cases, and 6.2% of MDR-TB sufferers are estimated to have Extensive Drug Resistant Tuberculosis (XDR-TB) cases. The development of antitubercular drug compounds with new mechanisms of action is needed to overcome cases of antibiotic resistance. The two-component PhoP-PhoR system in Mycobacterium tuberculosis which is related to bacterial virulence has the potential to become a new target protein for antitubercular compounds. This study uses a Dimer-Based Screening System method that utilizes the fusion of PhoR protein with the AraC repressor protein (AraC-PhoRMtb) in filtering candidates for antitubercular drug compounds. Drug compounds that have inhibitory activity of PhoR homodimerization will inhibit binding of the AraC repressor protein to the araC promoter which regulates the expression of GFP. The location of the interaction of potential compounds with fusion proteins is then estimated using molecular docking analysis. The aim of this research is to screen natural compounds which have the potential to become new antitubercular drug compounds. The presence and expression of pAraC-PhoRMtb plasmids in the Escherichia coli BL21 (DE3) culture of the transformants were successfully confirmed by PCR, DNA base sequencing, SDS-PAGE, and culture fluorescence tests. Fifteen isolates from naturally-occurring compounds as candidates for antitubercular compounds were screened using the system at a concentration of 12.5 ppm using DMSO as solvent. From these tests, it was found that 1 of the 15 isolates tested had significant inhibitory activity of AraC-PhoRMtb fusion protein inhibition, which was shown by laevifonol compound. Based on molecular docking analysis, laevifonol is predicted to interact with the dimerization domain to inhibit the formation of AraC-PhoR fusion protein dimers. From this study, it was concluded that laevifonol has the potential to be developed into a new antitubercular drug by inhibiting the dimerization of PhoR cytoplasmic domain in Mycobacterium tuberculosis.